O curso de licenciatura em educação física e os desafios da formação profissional: o processo de ensinar e aprender a docência - Ilha, Franciele Roos da Silva (2010)
The following paper conveys the Researching Approach of Formation, knowledge, and Professional Development (PPGE/CE/UFSM) and aimed to comprehend the articulation of development actions in the Majoring of Physical Education at the CEFD/UFSM with school teaching. It is justified due to the importance in comprehending the way recent breakthroughs performed in the curricular structures from the promulgation of National Curricular Guidelines for Basic Education Teachers and the National Curricular Guidelines for the Majoring in Physical Education are being target of discussion, reflection, and transformation in the context of the UFSM. The methodological approach adopted followed the assumptions of a qualitative approach case study. The facilities used for the study were the ones of the Center for Sports and Physical Education of the Federal University of Santa Maria. Information has been collected through document analysis and semi-structured interviews with teachers and students from this majoring. In order to interpret the information collected, content analysis has been used, emphasizing the following aspects: a) the PPP aims to give basis to the training processes developed in the majoring considering that it has a strict relationship with teachers in school b) the spaces for the teacher licensing courses compose the minority when compared to the ones for bachelor degree, even though, they are concerned about the training of future physical education teachers, since they deal with aspects of teaching School Physical Education. This finding has been reaffirmed after the conclusion that these spaces are in training places, since their participants attributed meaning to them and c) the processes of teaching and learning to be a teacher still represent a challenge to get Degree from the Physical Education Center because according to the participant students, some teachers develop their educational practice based on the model of technical rationality and/or do not approach the aspects of teaching in the subjects they teach. Fortunately, it has been identified the fact that there are teachers who make the dialogue of the school teaching in their pedagogical practices. Concerning students practices, teachers make clear that the undergraduate students are aware of the professional role they will have after graduating. Students, when referring to their performance in classes and training in other formative spaces and ways, they emphasize different aspects and distinct ways of taking part in the majoring. Nevertheless, all of them say they are interested in learning the necessary formative knowledge to teach. It was concluded that teacher licensing courses in Physical Education at the Physical Education Center of the Federal University of Santa Maria articulate their educational actions to school teaching, since the majoring is in general towards this direction. Before such situation, it is emphasized the relevance of the development of teaching practices to educational processes that involve work with School Physical Education.